What Can Humans Cognize about the Self from Experience? Comments on Corey Dyck’s “The Development of Kant’s Psychology during the 1770’s” - Patricia Kitcher (Con-textos Kantianos: International Journal of Philosophy, 2016)
I agree with Dyck’s basic claim that Kant follows the methodology of Rational Psychology in setting up his critique of it: He starts as it starts, with an existential proposition ‘I think.’ On the other hand, I am not convinced of Dyck’s use of the Dreams essay in establishing a timeline for the development of Kant’s views on inner sense. That essay is evidence that Kant thinks that Schwendenborg’s metaphysics is ungrounded, because he has a crazy sort of inner sense, but it does not show that Kant rejected a more standard internal sense at this time. I also suggest that some of Kant’s vacillation about inner sense depends on an unusual feature of his doctrine of the representations of space and time: They are composed of both sensory and a priori elements. My hypothesis is that the seeming vacillation about inner sense may be a reflection of whether whether he is considering it broadly, as a faculty that provides intuitions with a particular form, or whether he is restricting what it provides to what can be sensed.